(untitled) (Research, Society and Development, 2021)
The causes of pyometra are abnormal interactions between the uterus, circulating hormones and bacteria. Occurs in female dogs and cats. The use of contraceptives and undesirable mating can be predisposing factors. This disease is classified in two forms, the closed form is when the uterine cervix is ​​occluded and presents an accumulation of infectious material, with an increase in uterine volume and a process of systemic intoxication. In the open form, there is expulsion of uterine secretion and milder clinical signs. The aim of this study was to report the treatment with the use of aglepristone and gentamicin in uterine infusion in two five-year-old pug dogs with pyometra. Two non-castrated bitches were treated at the Veterinary Hospital of a higher education institution, for presenting clinical signs compatible with pyometra. Assessments of hematological and biochemical parameters were performed. Where they were treated with the uterine lavage method with Gentamicin Uterine Infusion and Aglepristone. In the blood count exams of the animals reported, alterations were observed in the white series of both bitches, these alterations being called leukocytosis by neutrophil in animal one and leukocytosis by neutrophil and eosinophilia in animal two. At the end of the treatment, complete recovery of the animals to pyometra can be observed. The treatment performed proved to be satisfactory with the use of gentamicin in the uterine lavage method. The bitches in the study will resume their reproductive activities, and artificial insemination is indicated to prevent the recurrence of the pyometra.